Performance of Coastal Waste Management Policy: Study in Tanjungpinang City - Nazaki; Eki Darmawan; Annissa Valentina (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Since the ocean unites all nations, the problem of coastal waste affects the livelihoods of many people around the globe. In addition, of course, it is related to the biological resources contained therein. The case in Tanjunginang City, for example, the problem of non-organic waste in several coastal areas of Tanjungpinang City, which reaches a thickness of approximately 3.5 meters, shows the importance of waste management, which is a field related to the arrangement of stockpiling, temporary stockpiling, transfer, processing, and the final disposal of waste. In a manner that follows the best principles of public health, economics, engineering, nature protection (conservation), beauty, and other environmental considerations taking into account public attitudes. Based on these facts, it is essential to place social policies whose determination requires a long and complicated process in the proper context, namely, understanding a political process in a balanced way. Therefore, existing policies need to be in context as a first step to see the problem of coastal waste and then strengthened by analyzing the performance of waste management policies carried out by the government. This study uses a qualitative approach by looking holistically at a problem and will be mapped based on social policies needed by the community. The aim is to provide an overview of the policy results of coastal waste management in Tanjungpinang City. The results of this study indicate that policy performance problems arise that do not accommodate the problem of coastal waste and other impacts on society.